IT, Organizational Change and Wages - Alexandra Spitz; Irene Bertschek (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
In this paper we analyze the impact of information technology and organizational changes on wages using individual level data for 1998/1999. The average impact of IT use on wages turns out to be five to six percent, however, the effects differ across different IT components. Unless employees use IT at the workplace, they do not share in the gains from organizational changes in form of higher wages. Outsourcing additionally requires a high qualification of employees in order to result in positive wage effects.
Keywords: J30; J31; 330; Information technology; organizational change; wage equations; Lohn; Informationstechnik; Computergestütztes Verfahren; Organisatorischer Wandel; Outsourcing; Schätzung; Deutschland